Advokasi dan Perlindungan Anak di PAUD Hubbul Wathon Sei Berombang - Shadilla Shadilla (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the implementation of child advocacy and protection at Hubbul Wathon Sei Berombang Early Childhood Education (PAUD) as an effort to create a safe, comfortable, and child-friendly educational environment. Child protection in Early Childhood Education (PAUD) institutions is a crucial aspect in supporting optimal child growth and development, particularly in addressing various forms of violence, discrimination, neglect, and violations of children's rights in the educational environment. This study used a qualitative approach with field study methods. Data collection techniques included observation, interviews, and documentation with the principal, teachers, parents, and students. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of child advocacy and protection at Hubbul Wathon Sei Berombang PAUD is carried out through several strategies, namely: (1) implementing child-friendly school policies; (2) supervising and mentoring students; (3) active communication between teachers and parents; (4) instilling moral and religious values; and (5) providing education on children's rights to the entire school community. Furthermore, the institution also strives to prevent violence and bullying through persuasive approaches and character development for children. However, this study identified several obstacles, such as limited parental understanding of child protection, minimal supporting facilities, and suboptimal collaboration with external parties related to child protection. This study concluded that child advocacy and protection at the Hubbul Wathon Sei Berombang PAUD has been running quite well, but still requires strengthening in terms of socialization, collaboration between parties, and the development of sustainable child protection programs. This research is expected to serve as a reference for PAUD institutions in improving the quality of child protection in educational settings.